2001
DOI: 10.2337/diabetes.50.1.166
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Vasorelaxant Effect of Carbon Monoxide in Diabetes and the Underlying Mechanisms

Abstract: Carbon monoxide (CO) is an endogenous gaseous factor that relaxes vascular tissues by acting on both the cGMP pathway and calcium-activated K + (K Ca ) channels. Whether the vascular effect of CO is altered in diabetes had been unknown. It was found that the CO-induced relaxation of tail artery tissues from streptozotocininduced diabetic rats was significantly decreased as compared with that of nondiabetic control rats. The blockade of the cGMP pathway with ODQ (1H-[1,2,4]oxadiazolo[4,3,-a]quinoxalin-1-one) co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 44 publications
(53 reference statements)
1
23
0
Order By: Relevance
“…26 Also, it has been reported that inhibition of sGC attenuated the stimulatory effect of CO on BK channels in smooth muscle cells. 19 The finding that inhibition of sGC prevents the early effect of CO on BK channels suggests that the stimulatory effect of CO depends, at least in part, on the activation of sGC in endothelial cells. However, the observation that inhibition of sGC failed to abolish the stimulatory effect of CO on BK channels suggests that CO stimulates BK channels via a cGMP-independent mechanism.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…26 Also, it has been reported that inhibition of sGC attenuated the stimulatory effect of CO on BK channels in smooth muscle cells. 19 The finding that inhibition of sGC prevents the early effect of CO on BK channels suggests that the stimulatory effect of CO depends, at least in part, on the activation of sGC in endothelial cells. However, the observation that inhibition of sGC failed to abolish the stimulatory effect of CO on BK channels suggests that CO stimulates BK channels via a cGMP-independent mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has been shown that CO caused vasodilation by activation of BK channels and suppression of voltagedependent Ca 2ϩ channel activity in the smooth muscle. 14 This mechanism could play an important role in mediating CO-induced vasodilation in the rat-tail artery 19 and rat gracilis muscle arterioles. 13 There are several mechanisms by which CO activates BK channels: (1) CO could increase NO release, which, in turn, activates BK channels; (2) CO could increase the production of superoxide, alter redox signaling, and increase the production of superoxide anions; (3) CO stimulates sGC and increases cGMP formation in endothelial cells; and (4) CO activates BK channels by direct modification of BK channel protein.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Direct evidence for the role of CO in vascular response was presented when it was shown that a reduction in CO generation resulted in increased vascular resistance in rat liver (Suematsu et al, 1994). Subsequent studies have clearly shown that HO-1-derived CO and bilirubin result in a vasorelaxant effect not only via cGMP-dependent but also via cGMP-independent (Ollinger et al, 2007;Li et al, 2008) stimulation of certain K channels Wang et al, , 2001Dong et al, 2007) and an increase in adiponectin levels (L'Abbate et al., 2007). Furthermore, it is considered unlikely that CO and NO represent redundant messenger molecules, even though both are active in the vessel wall.…”
Section: Carbon Monoxide Production Ho-dependent Ho-independentmentioning
confidence: 99%